2018
DOI: 10.1186/s12937-018-0346-x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial to test the effectiveness of a locally-produced ready-to-use supplementary food (RUSF) in preventing growth faltering and improving micronutrient status for children under two years in Cambodia: a study protocol

Abstract: BackgroundExisting ready-to-use supplementary and therapeutic foods (RUSFs and RUTFs) have had limited acceptance and effectiveness in Cambodia. This has hampered the treatment and prevention of child malnutrition. An innovative, locally produced, multiple micronutrient fortified lipid-based nutrient supplement (LNS) has been developed for use as an RUSF. Unlike most RUSFs, which contain milk, this product contains fish as the animal protein. Few RUSFs have been formulated using non-milk animal-source foods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The RUF could be either provided freely through nongovernmental organisation (NGO) programs or sold at the market. A middle model, which caregivers favour, would be for community health volunteers to sell RUF [44]. This kind of public/private production and distribution model should be explored further.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RUF could be either provided freely through nongovernmental organisation (NGO) programs or sold at the market. A middle model, which caregivers favour, would be for community health volunteers to sell RUF [44]. This kind of public/private production and distribution model should be explored further.…”
Section: Resultsmentioning
confidence: 99%
“…All groups continued to experience growth faltering, although the RUSF group faltered at a lower rate. Details on the effectiveness trial are described elsewhere [43], and results are forthcoming [44].…”
Section: Methodsmentioning
confidence: 99%
“…Other researchers who have worked on small quantity LNSs (20‐50g/day) have found that in small quantities, LNSs may improve growth (Dewey et al, ; Hess et al, ). They may also improve appetite (Arimond et al, ; Lesorogol, Jean‐Louis, Green, & Iannotti, ), something which caregivers in our acceptability trial remarked upon (Borg et al, ). This finding warrants a trial of the RUSF in small quantities.…”
Section: Discussionmentioning
confidence: 65%
“…All processing was conducted in certified facilities, and microbiological safety testing was conducted regularly. The ingredients of the RUSF and the comparators are detailed in Tables A1 and A2, and in the acceptability and effectiveness protocols (Borg et al, ; Borg et al, ). The RUSF was provided as a medium quantity supplementary food, that is, providing 50‐100% of the child's daily energy requirements (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Locally produced ready-to-use therapeutic food (RUTF) was also proven to be effective in preventing growth faltering and improving micronutrient status [19,20]. Nevertheless, according to Sigh et al, the provision of local foods combined with CEN did not improve young child nutritional status as compared to CEN alone.…”
Section: Food-based and Nutritional Interventionsmentioning
confidence: 99%